Depositional provenance of the Himalayan metamorphic core of Garhwal region, India: Constrained by U–Pb and Hf isotopes in zircons - Spencer, Christopher; Harris, R.; Dorais, M.J. (Elsevier BV, 2012)
U–Pb and Hf isotopes in zircon from the highly metamorphosed core of the Himalaya in the Garhwal region of India indicate that the ortho- and paragneiss units of the Greater Himalayan Sequence (oGHS and pGHS, respectively) are geochemical distinct from the older Lesser Himalayan Crystalline Sequence (LHCS). Zircon grains from Paleoproterozoic metasediment of the LHCS yield U–Pb crystallization ages from 1614 ± 14 Ma to 2679 ± 14 Ma with a single distinct peak in the age spectra at 1870 Ma. εHf values from zircon in the LHCS range from 1 to − 8. In contrast, zircon grains from the Neoproterozoic pGHS yield U–Pb crystallization ages from 481 ± 10 Ma to 2560 ± 8 Ma with a single distinct peak at 860 Ma. εHf values from these zircons range from 13 to − 21. The oGHS yields zircon grains with U–Pb crystallization ages from 416 ± 2 Ma to 2740 ± 2 Ma with a single distinct peak at 472 Ma. These grains often exhibit older inherited cores ranging from ~ 800 Ma to ~ 2740 Ma with Ordovician rims (416 Ma to 510 Ma). The εHf values of zircon grains in the oGHS have two distinct modes: the ~ 860 Ma inherited zircon cores have a similar range to the ~ 860 Ma zircons from the pGHS (13 to − 21), whereas the ~ 480 Ma rims range from − 7 to − 11.The detrital zircon U–Pb age spectra from the pGHS in the Garhwal region differs significantly from the U–Pb age spectra in other parts of the range (Nepal and Bhutan). These differences indicate wide lateral variations in provenance for the various source regions of the pGHS. Comparisons of the U–Pb and Hf data from the Garhwal region with potential ~ 1800 Ma source regions show overlap with metasediments of the Aravalli shield of India. In the pGHS the most juvenile εHf values overlap with those of the northern Arabian Nubian Shield in Israel. However, these rocks show little crustal contamination at ~ 800 Ma, whereas the pGHS has significant crustal contamination at ~ 860 Ma. The Ordovician oGHS has εHf values that match the average εHf values of the paragneiss implying that it was sourced from the paragneiss. Although the nature of this Ordovician igneous event is still poorly understood, it is clear that the Hf isotopes can provide further insight into the petrogenesis of the magmatic rocks associated with it.